Determinants of communication between partners about STD symptoms: implications for partner referral in South Africa - A. Meyer-Weitz; P. Reddy; B. van den Borne; G. Kok; J. Pietersen (South African Family Practice)
Background: STDs as preventable diseases are a major public health problem in South Africa, both in terms of their effect on quality of life, their economic costs and the fact that STDs as co-factors drive the HIV epidemic. Their widespread occurrence and high prevalence rates are cause for concern. It is argued that the duration of infection increases the probability of harmful sequelae and STD transmission, including HIV, to others. The promotion of seeking health care for STD symptoms at an early stage and partner referral for STD treatment are important strategies in preventing STD transmission to others and re-infection of partners. The cost implications of contact tracing by healthcare workers has resulted in patients being encouraged to refer their partners for STD treatment. This has not always been effective, despite efforts to improve partner referral rates by improved “contact cards” (i.e. a card with a code representing the STD that the patient has been treated for to be given to sexual partners as a way to speed up treatment) and more accessible healthcare services. Other studies have found that the proportion of clients who present with contact cards at STD services ranged from about 2% to 39%, while the proportion of partners who were referred for treatment range from 16% to 30%. Mathews et al. argue that returning contact cards might not be a sensitive enough proxy indicator for partner referral rates. Partner referrals have been found to be seriously compromised by patients' causal explanations for STDs, as well as by the unequal power of the genders in sexual relationships, which impacts on the patients' ability to communicate about sexual matters. Patients often lack an understanding of the importance of referring their asymptomatic partners for treatment. Women's inability to discuss sexual issues due to their unequal status in sexual relationships might impact on partner referral behaviour. Men have been found to blame the STD on the “outside women” (sexual partners outside the primary relationship) and are therefore less likely to refer these partners. The conflict that could arise from informing a partner about an STD was viewed by men as a reason not to communicate about having a STD. While the ability to communicate about STDs with sexual partners is an essential prerequisite for referring them for medical treatment, little attention has been paid to understanding this process. This study is aimed at gaining some understanding of the determinants of communication between partners about STD symptoms. In this study, “talking with a partner about STD symptoms” before seeking medical treatment was viewed as an indication of the likelihood of future partner referral behaviour.